Nature and Preoperative Prediction of Difficult Non-Channeled Video-Laryngoscopic Tracheal Intubation in Otorhinolaryngological Surgery: A Retrospective Cohort Study of 1932 Adults - Darhae Eum; Hyoung Woo Chang; Myoung Hwa Kim; Jinmok Kim; Wyun Kon Park; Hyun Joo Kim (Journal of Clinical Medicine, 2026)
Background/Objectives: Video laryngoscopy improves the glottic view, yet difficult intubation still occurs. Whether it reflects a poor view or arises despite an adequate one is rarely quantified in otorhinolaryngological surgery. We described this pattern and its preoperative predictors. Methods: In a single-center retrospective cohort of 1932 adults undergoing otorhinolaryngological surgery with non-channeled video laryngoscopy (2018–2021), difficult intubation was defined a priori as two or more laryngoscopic attempts (blade insertions), a lower bound on difficulty. The glottic view (Cormack–Lehane grade) and intubation time described the difficulty, and predictors were identified by logistic regression. An unweighted count of four anatomical bedside factors, selected on rationale (not data-driven significance) at pre-existing clinical thresholds, was the primary risk score; a five-factor version added a resident operator. Results: Difficult intubation occurred in 120 patients (6.2%; 95% CI 5.2–7.4). Most occurred despite an adequate view (64% at Cormack–Lehane grade I–II; 45% at grade I alone); the rate was 4.3% (95% CI 3.5–5.4) versus 29.3% (95% CI 22.5–37.1) for good versus poor views (odds ratio 9.2, 95% CI 6.0–14.0), and difficult intubations took about twice as long (median 90 versus 40 s). Independent predictors were shorter inter-incisor and thyromental distances and a resident operator. The four-factor count graded risk from 4.6% to 12.9% (odds ratio 1.63 per factor; apparent area under the curve 0.596, 95% CI 0.546–0.645, not corrected for optimism; positive predictive value 8.8% at one or more factors), and a five-factor count performed similarly (0.631). Within the good-view subgroup, difficulty appeared to relate more to operator inexperience than to anatomy (adjusted odds ratio 2.48 versus 1.13). Conclusions: Difficulty was far more likely with a poor view, but because a good view occurred in 92.4% of patients, most difficult intubations arose despite an adequate one. We hypothesize that difficulty then lies in tube delivery rather than visualization; because the analysis conditions on the view, this needs prospective testing. Discrimination was modest and the count exploratory; these single-center findings require external validation.